EFEKTIVITAS PEMBELAJARAN PROGRAM SEKOLAH LIMA HARI (PS5H) DI SMK NEGERI 1 SAWIT BOYOLALI - Candraningrum, Novia Ayu; Suharno, Suharno; Rohman, Ngatou (Nozel : Jurnal Pendididikan Teknik Mesin, 2020)
The Five Day School is a learning program in schools that lasts five days a week. This is an educational innovation that aims to improve the quality of education through the effectiveness and efficiency of the use of time in school. The purpose of this program is to help students be able to share time well between academic and non-academic activities which are both very much needed for student development. This study was conducted at SMK Negeri 1 Sawit Boyolali with a qualitative methode approach as a research procedure that produces qualitative descriptive data used is descriptive qualitative data analysis techniques, because the data obtained is in the form of captions. Descriptive data analysis about the effectiveness of implementing five-day school program learning. The results showed that the implementation of PS5H learning at SMK Negeri 1 Sawit Boyolali was implemented well. Teachers of SMK Negeri 1 Sawit Boyolali have given teaching appreciation by improving their abilities and skills by paying attention to lessons in class. The use of time with the application of PS5H teaching and learning hours is carried out effectively and provides a time off on Saturdays and learning outcomes at SMK Negeri 1 Sawit Boyolali are expected to achieve teacher during the 100% targeted teaching process with a remedial target. If the remedial has not yet reached the KKM, assignments will be given until they are able to reach KKM